CHARACTER STRENGTHENING IN THE IMPLEMENTATION OF THE 7 HABITS OF GREAT INDONESIAN CHILDREN TOWARDS THE GOLDEN GENERATION - Astutik, Kurniah (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Character strengthening is an important foundation for early childhood towards Indonesia's golden generation in 2045. The purpose of this study is to analyze character strengthening in the implementation of the 7 habits of great Indonesian children in the educational and family environment. This research used a qualitative descriptive approach with a case study method at Babus Salam Kindergarten in Bandilan Prajekan. Data triangulation was conducted to strengthen the analysis results by observing educators, parents, and the surrounding environment. Interviews were conducted not only with educators and parents but also with class associations and the school committee, which spearheads school activities. Thus, the collected documentation can support the recording and strengthening of data. The results of the study indicate that the implementation of the 7 habits of great Indonesian children in daily habits, both at school and at home, has a significant impact on strengthening children's character. This is further enhanced by the support and collaboration between educators, parents, and the surrounding community. It is recommended that the synergy between educators, parents, and the community be continuously enhanced by creating programs involving all relevant stakeholders and parenting activities to strengthen collaboration between educators and parents in educating children, conducting seminars or mentoring sessions with child psychologists, and other activities that support character building. This will enable Indonesia to move towards a more focused Golden Generation, with strong character, and be ready to face future challenges.